The evolution of family-centered care - Jolley, J.; Shields, Linda (Elsevier, 2009)
Aim: The aim of this study is to explore the history of family-centered care (FCC). Background: FCC was developed after World War II, when nursing, then deeply paternalistic, had become asynchronous with changing social expectations for the care of hospitalized children. Methods: This is a historical review of literature reflecting development of pediatric models of care using publications of classic theorists and others. Results: Development of FCC resulted from work by U.S. and UK researchers,theorists, and advocates. Their research was right for its time, and its acceptance was the result of social readiness for change resulting from people's experience of World War II. Conclusion: World War II brought about changes enabling emergence of lobby groups concerned with children in hospital, awakening of pediatric health professionals to family-oriented practice, and development of models of care that allowed widescale adoption of FCC.